The use of Artificial Intelligence in newsrooms: proposals and limitations - Lopezosa, Carlos (2024)
The motivation of this research is the identification and exploratory analysis of journalistic projects implemented with artificial intelligence. Furthermore, the main objective is to determine how the media is implementing artificial intelligence in newsrooms. The methodology employed is scoping review, which involves systematic exploration of grey literature (reports), complemented by a descriptive analysis of the identified journalistic products. Thanks to this work, not only have different journalistic projects supported by AI been analyzed, but their limitations have also been identified. This research concludes with evidence-based contributions to the debate on the current and future effects of AI in the journalism sector, with a focus on ethics.